Lack of pharmacokinetic interaction between derazantinib and naringin in rats. (31st December 2023) - Liu, Ya-nan; Chen, Jie; Xu, Xinhao; Hu, Yingying; Hu, Jin-yu; Xu, Ren-ai; Lin, Guanyang
Abstract: Context: Derazantinib—an orally bioavailable, ATP competitive, multikinase inhibitor—has strong activity against fibroblast growth factor receptors (FGFR)2, FGFR1, and FGFR3 kinases. It has preliminary antitumor activity in patients with unresectable or metastatic FGFR2 fusion-positive intrahepatic cholangiocarcinoma (iCCA). Objective: This experiment validates a novel sensitive and rapid method for the determination of derazantinib concentration in rat plasma by ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS), and applies it to the study of drug-drug interaction between derazantinib and naringin in vivo . Materials and methods: A Xevo TQ-S triple quadrupole tandem mass spectrometer was used for mass spectrometry monitoring in selective reaction monitoring (SRM) mode with transitions of m/z 468 96 → 382.00 for derazantinib and m/z 488.01 → 400.98 for pemigatinib, respectively. The pharmacokinetics of derazantinib (30 mg/kg) was investigated in Sprague-Dawley (SD) rats divided into two groups (with the oral pretreatment of 50 mg/kg naringin or not). Results: The newly optimized UPLC-MS/MS method was suitable for the determination of derazantinib in rat plasma. It was also successfully employed to evaluate the effect of naringin on derazantinib metabolism in rats. After pretreatment with naringin, there was no significant difference in the pharmacokinetic parameters (AUC0→t, AUC0→∞, t1/2, CLz/F, and Cmax ) of derazantinib when compared with derazantinib alone. Conclusion: Co-administration of naringin with derazantinib was not associated with significant changes in pharmacokinetic parameters. Thus, this study suggests that the combination of derazantinib with naringin can safely be administered concomitantly without dose adjustment.